Prevalence of measurable residual disease in patients with refractory/relapsed multiple myeloma who reached complete response: a cross-sectional multicentric study - Neves, Manuel; Gerivaz, Rita; Esteves, Graça; Bergantim, Rui; Ferreira, Gisela; Coelho, Henrique; Afonso, Celina; Duarte, Delfim; Neves, Anabela; Silva, Helena Matos; Caetano, Joana; Jaime, Rita; et al. (Frontiers in Hematology, 2024)
BackgroundMultiple myeloma (MM) is an incurable hematologic malignancy, and even though the complete response (CR) rate has been growing, a high percentage of patients continues to relapse. Recent research showed that most relapses may be related to the persistence of measurable residual disease (MRD). In this study, we intended to evaluate the MRD status in MM patients who reached CR in their second or third lines of treatment.MethodsThis was a cross-sectional, multicentre, non-interventional study to describe the MRD status in patients with relapsed or refractory MM (rrMM), with documented CR; adult male and female patients, from 11 Portuguese sites, in their second or third line of treatment were included. Bone marrow MRD was assessed through next-generation flow cytometry (NGF) technology.ResultsAmong the 68 subjects who gave informed consent, 48 were considered eligible for the study. Of the 48 subjects with confirmed CR, 31 (64.6%) had undetectable MRD levels. The incidence of undetectable MRD was lower in International Staging System (ISS) III patients compared with ISS I/II patients (60% vs. 70.8%; p = 0.45), and lower in patients treated without daratumumab-containing regimens compared with those treated with daratumumab-containing regimens (57.1% vs. 75.0%; p = 0.30). Notably, despite the small sample size, the incidence of undetectable MRD was significantly lower in patients with high-risk cytogenetics compared to those with standard risk (33.3% vs. 76.0%; p = 0.04).DiscussionOur results highlight the possibility of achieving undetectable MRD in the rrMM setting, especially in earlier stages and with highly effective protocols. We expect that this work leverages the implementation of larger real-world evidence studies in rrMM patients, in which MRD may also be defined as a primary endpoint.